2017
DOI: 10.1126/sciadv.1603258
|View full text |Cite
|
Sign up to set email alerts
|

Direct quantitative measurement of the C═O⋅⋅⋅H–C bond by atomic force microscopy

Abstract: Atomic force microscopy can image the hydrogen atoms of single molecules via very weak hydrogen bonding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
79
1
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(87 citation statements)
references
References 47 publications
3
79
1
4
Order By: Relevance
“…Thec hemical structure is resolved by atomic force microscopy (AFM) with CO-functionalized tips, [33] allowing the assignment of the spatial fingerprint of the Kondo resonance to distinct moieties.F inally,w er eveal the presence of as pecific bonding motif upon self-assembly, consistent with molecular dipole-dipole interactions.T he persistence of the Kondo resonance in the STS data indicates that the noncovalent intermolecular coupling does not affect the open-shell configuration of the molecule. [36] Ther est of the structure,l ying closer to the surface,can be better observed in the corresponding high-pass (Laplace) filtered image (Figure 1d), where the benzotriazinyl core is clearly resolved. [32] An STM image of the Blatter radical on Au(111) is shown in Figure 1b.…”
mentioning
confidence: 90%
“…Thec hemical structure is resolved by atomic force microscopy (AFM) with CO-functionalized tips, [33] allowing the assignment of the spatial fingerprint of the Kondo resonance to distinct moieties.F inally,w er eveal the presence of as pecific bonding motif upon self-assembly, consistent with molecular dipole-dipole interactions.T he persistence of the Kondo resonance in the STS data indicates that the noncovalent intermolecular coupling does not affect the open-shell configuration of the molecule. [36] Ther est of the structure,l ying closer to the surface,can be better observed in the corresponding high-pass (Laplace) filtered image (Figure 1d), where the benzotriazinyl core is clearly resolved. [32] An STM image of the Blatter radical on Au(111) is shown in Figure 1b.…”
mentioning
confidence: 90%
“…[37] Werden weniger verzerrte Bilder gewünscht, kann man die Spitze auch anders funktionalisieren, z. [34,35,[41][42][43][44][45] Bislang wurden viele ganz unterschiedliche Funktionalisierungen der Messspitze fürdie AFM-Bildgebung erkundet, darunter die folgenden:1 )Funktionalisierung mit Metallatomen wie Cu, Ag und Au.H ierfürw urde entweder die Spitze in ein Metallsubstrat eingetaucht oder es wurden einzelne Metall-Adatome auf einem NaCl-Film aufgehoben. [38] Bindungsartige Kontraste an der Position von Wasserstoffbrücken wurden auch mit STM- [39] und AFM-Techniken [10,40] beobachtet.…”
Section: Methodsunclassified
“…More recently, Shigeki Kawai et al also adopted a direct quantitative measurement of H-bond, using AFM, the outmost H atom of propellane molecules was found to form weak C=O···H-C H-bond with CO tip [117]. The result revealed that high frequency shift would present when the CO tip could possibly form H-bond with the outmost C-H parts, while potential energy analyses shows that such C=O···H-C H-bond is just above the onset of Pauli repulsion.…”
Section: Electronic Delocalization In H-bond Systemsmentioning
confidence: 99%